Longitudinal Association Between Child Psychological Abuse and Neglect and Academic Achievement in Chinese Primary School Children: A Moderated Mediation Model - Li, Jiajing; Li, Ziying; Lei, Xiuya; Yang, Jingyuan; Yu, Xiao; Liu, Haoning (Frontiers in Psychology, 2022)
To investigate the relationships among child psychological abuse and neglect (CPAN), children’s learning engagement, family socioeconomic status (family SES), and children’s academic achievement, 271 children (Mage = 9.41 ± 0.81 years old) and their parents participated in this study with a longitudinal design. Results revealed that learning engagement at T1 mediated the relationship between CPAN at T1 and academic achievement at T2 when gender, age, grade, and academic achievement at T1 were under control. Family SES at T1 moderated the relationship between children’s learning engagement at T1 and academic achievement at T2. The association between learning engagement and academic achievement was stronger among children from lower family SES. Our findings highlighted the negative impact of CPAN and the critical role of learning engagement in children’s academic achievement, especially for those from low SES families.